2016
DOI: 10.3390/met6020037
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Dissolution of γ’ Precipitates in IN792 Superalloy at Elevated Temperatures

Abstract: Precipitation of γ' phase in nickel-base superalloy IN792-5A was studied using in-situ Small Angle Neutron Scattering (SANS). It was found that additional precipitates are formed after reheating above 600˝C when the material is previously fast cooled (100 K/min) from 900˝C. The size distribution and volume fraction of the additional γ' precipitates as well as of the already present medium-size precipitates in dependence on temperature were evaluated. The small precipitates can influence mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In fact, the present results confirmed observations by other investigators [ 40 , 41 ], namely the precipitation of small particles of secondary γ’ from 600 to 875 °C determining an increase of IN792 yield stress and hardness. The phenomenon has been very carefully investigated by Strunz et al [ 42 ] through Small Angle Neutron Scattering (SANS) measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the present results confirmed observations by other investigators [ 40 , 41 ], namely the precipitation of small particles of secondary γ’ from 600 to 875 °C determining an increase of IN792 yield stress and hardness. The phenomenon has been very carefully investigated by Strunz et al [ 42 ] through Small Angle Neutron Scattering (SANS) measurements.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed before, the increase of hardness depended on the precipitation of secondary γ’ phase, due to the temperatures of PWHTs. In Strunz et al [ 42 ] it was reported that the precipitation of secondary γ’ in IN792 is maximum at about 725 °C, determining a significant increase of yield stress.…”
Section: Resultsmentioning
confidence: 99%
“…After several decades, the archetype of the superalloys, two-component Nichrome, was modified to such an extent that the alloying elements exceeded twelve. The best examples of this are the microstructurally complex superalloys as MAR-M247 and Inconel 792+Hf [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, the misfit measured for the standard heat treatment condition (solution + ageing), with a fully coherent γ phase, is not the equilibrium value, but a constrained value for the superalloy [23][24][25]. The start temperature of γ dissolution (T sd ) for Inconel 738, determined by Zla [26] by differential thermal analysis, was reported to be between 914 and 957 • C, depending on the heating rate, and for Inconel 792, Strunz [27] showed T sd to be below 900 • C. In PM Astroloy, the start of dissolution occurred between 800 and 850 • C [28]. Sponseller [29] calculated γ solvus temperature (T s ) for some superalloys to be between 1189 • C (equiaxed René 95) and 1307 • C (CMSX-2), and so the interval was also relatively wide.…”
Section: Introductionmentioning
confidence: 99%